Development of the P5 Module (Adipura Module) with The Entrepreneurship Theme for Elementary School Students as An Effort to Strengthen the Values of The Pancasila Student Profile - Azizah, Azizah; Wahyuni, Sri; Asriani, Asriani; Hardianti, Sri; Rosnadi, Rosnadi; Naimi, Nadlrah; Sitepu, Melyani Sari (Jurnal Paedagogy, 2024)
This research aims to develop the P5 Adipura Module with the theme of entrepreneurship for elementary school students as an effort to strengthen the values of the Pancasila student profile (P3). The research method used was research and development adopting Sugiyono's development model with 7 stages including potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The test subjects were students in class 4 phase B elementary school. The trial was carried out in small groups. The data collection process was in the form of interviews, observations, and distributing questionnaires. Data analysis uses quantitative and qualitative descriptives. The result of this research was a product in the form of the P5 Adipura Module on the use of family medicinal plants (TOGA) on the theme of entrepreneurship. The average result of material expert validation was 3.29 with valid criteria. Likewise, the average media expert validation result was 3.20 with valid criteria, suitable for use in the project learning process by educators and students. Experiments in small groups to show the practicality of the module can be seen from the score interval obtained from the practicality sheet instrument by users (teachers and students) of 3.86 with very practical criteria. The Adipura P5 module is suitable for use, making it easier for educators and students in the learning process.